C-reactive protein, interleukin-6 and tumor necrosis factor alpha as predictors of incident coronary and cardiovascular events and total mortality. A population-based, prospective study - Tuomisto, Karolina; Jousilahti, Pekka; Sundvall, Jouko; Pajunen, Pia; Salomaa, Veikko (Thrombosis and haemostasis, 2006)
Previous studies have shown an association between serum C-reactive protein (CRP) and cardiovascular disease (CVD) risk. The roles of interleukin-6 (IL-6) and tumor necrosis factor alpha (TNFalpha) are less well established. The aim of the present study was to analyze the associations of CRP, IL-6 and TNFalpha with incident coronary heart disease (CHD) events, CVD events, and total mortality. A random population sample, including men and women aged 25-64 years was examined in Finland in 1992. The sample size was 7,927 and 6,051 (76%) participated. The cohort was followed up until the end of 2001. During the follow-up, 151 incident CHD events, 205 CVD events and 183 deaths from any cause were observed. A stratified random subsample (n=313) was used as the comparison group. After adjustment for conventional CVD risk factors, CRP showed a significant association with CHD risk in men (HR=2.39, 1.08-5.28, comparing fourth quartile to the first quartile). This association remained significant after further adjustment for TNFalpha. TNFalpha also was a significant predictor of CHD among men, but the association was nonlinear (HR=2.21, 1.18-4.14 comparing the three upper quartiles to the first quartile). Further adjustment for CRP did not change this association substantially. Both CRP and TNFalpha predicted also all CVD events and total mortality among men. Among women the findings were nonsignificant. In conclusion, CRP and TNFalpha were significant, independent predictors of CHD and CVD events and total mortality among men. These findings provide further support to the important role of inflammation in the pathogenesis of CVD.